Prevalence of type 2 diabetes mellitus among adults aged between 30 to 60 years residing in rural area: a cross sectional study - M. P., Poornima; Walvekar, Padmaja R. (International Journal Of Community Medicine And Public Health, 2018)
Background: The burden of diabetes mellitus is expected to increase by 58%, from 51 million people in 2010 to 87 million in 2030. In rural India the prevalence rate has increased from 1% to 4-10% over last 20 years. Objective of the study is to know the prevalence of type 2 diabetes mellitus among adults aged between 30 to 60 years residing in rural area. Methods: This community based cross-sectional study was carried out Agasga, the rural field practice area of Dept. of Community Medicine, among 855 adults aged between 30-60 years by using a predesigned & pretested schedule. Statistical analysis was done using percentages and Chi square test. Results: In this study, 67.24% participants were in age group 30-49 years, 32.74% between 50 to 60 years. 48.53% were male and 51.54% were female participants. 79% of the participants were heavy workers, 17.5% were moderate workers and rest 3.5% were sedentary type of workers. 10.9% were illiterate, and rest 91.1% was literates. 69.3% are BPL card holders. The prevalence of diabetes was 9.5%; 10.8% were at risk of getting Diabetes Mellitus. This gender wise difference in diabetes mellitus was not found to be statistically significant (p=0.986). Conclusions: With high degree of heritability, life style factor diabetes could become a major health hazard in India and this underscores the fact that prevention of diabetes must be one of the important health targets for the nation in this century. Early identification of risks will help in prevention and burden of disease.